Alkaloids Isolated in the Roots of Aconitum carmichaeli Debx Growing in Vietnam - Vu, Duc Loi (2016)
The roots of Aconitum Carmichaeli Debx. is recognized as a medicinal plant by its anti-inflammatory and analgesic effects. Our phytochemical investigation of the roots led to the isolation of three alkaloids including delcosine (1), fuziline (2), and karacoline (3). Their structures were identified on the basis of NMR, MS, IR spectroscopic analysis and comparison with the published NMR data. Compound 1 was isolated for the first time from this plant